Effect of application frequency of Bacillus amyloliquefaciens endophyte on Moniliophthora roreri under field conditions (Bioagro, 2025)
The use of endophytic bacteria of the genus Bacillus as biocontrol agents against Moniliophthora roreri is presented as an environmentally effective option in agriculture. The objective was to evaluate the effect of the application of endophytic B. amyloliquefaciens against the causal agent of moniliasis in cocoa. The experiment was conducted in a 14-year-old cocoa plantation, under a 3 x 3 m frame, in a randomized complete block design, with three treatments (frequency of application: 15, 30 and 45 days) and five replications. During the 90 days of development at a biweekly frequency, incidence and external severity were evaluated on the pod. At harvest time, the pods were opened and the percentage of internal severity was determined. Also, endophytic colonization was determined. It was found that six applications of spore suspension had a biocontrol effect on M. roreri, with average incidence between 1.0 and 4.1 %, external severity between 1.8 and 8.5 %, internal severity between 5.9-6.3 % and endophytic colonization between 7.3-7.5 x 108CFU g-1 of plant tissue. The application of the bacteria, at a fortnightly frequency, had a biocontrol effect on M. roreri, with average incidence values between 1.0 and 4.1 %, external severity between 1.8 and 5.0 %, internal severity between 5.9-6.3 % and endophytic colonization between 7.3-7.5 x 108 CFU g-1 of plant tissue. The biweekly application frequency demonstrated a biocontrol effect on M. roreri due to its high capacity for endophytic colonization, without differences with the control, presenting itself as a biological alternative to reduce the effects caused by the moniliasis in cocoa agroecosystems.
Keywords: Biological control; cacao; endophytic Bacillus; field; frosty pod rot